Advanced economic theory : micro- and macroeconomics - Jhingan, M. L. (New Delhi : Vrinda Publications ; New York : Advent Books [distributor], 2001)
Features lucid yet critical exposition of classical, neo-classical and modern concepts and theories relating to microeconomics; critical explanation of the classical and Keynesian theories of income, output and employment; extensive critical analysis of the nature and theories of business cycles and two entirely new parts on international trade and economic development and planning.
Includes bibliographical references.
oif 17/04/2015
Loans
Keywords: Economics; Microeconomics; Macroeconomics; Economic theory